Progressive multifocal leukoencephalopathy in a patient post allo-HCT successfully treated with JC virus specific donor lymphocytes - Maximilian Steinhardt; Eliza Wiercinska; Manh Van Pham; Götz Ulrich Grigoleit; Alessandro Mazzoni; Matteo C. Da Vià; Xiang Zhou; Katharina Meckel; Katharina Nickel; Johannes Duell; Franziska Krummenast; Sabrina Kraus; et al. (2020)
Abstract Background Progressive multifocal leukoencephalopathy is a demyelinating CNS disorder. Reactivation of John Cunningham virus leads to oligodendrocyte infection with lysis and consequent axonal loss due to demyelination. Patients usually present with confusion and seizures. Late diagnosis and lack of adequate therapy options persistently result in permanent impairment of brain functions. Due to profound T cell depletion, impairment of T-cell function and potent immunosuppressive factors, allogeneic hematopoietic cell transplantation recipients are at high risk for JCV reactivation. To date, PML is almost universally fatal when occurring after allo-HCT. Methods To optimize therapy specificity, we enriched JCV specific T-cells out of the donor T-cell repertoire from the HLA-identical, anti-JCV-antibody positive family stem cell donor by unstimulated peripheral apheresis [1]. For this, we selected T cells responsive to five JCV peptide libraries via the Cytokine Capture System technology. It enables the enrichment of JCV specific T cells via identification of stimulus-induced interferon gamma secretion. Results Despite low frequencies of responsive T cells, we succeeded in generating a product containing 20 000 JCV reactive T cells ready for patient infusion. The adoptive cell transfer was performed without complication. Consequently, the clinical course stabilized and the patient slowly went into remission of PML with JCV negative CSF and containment of PML lesion expansion. Conclusion We report for the first time feasibility of generating T cells with possible anti-JCV activity from a seropositive family donor, a variation of virus specific T-cell therapies suitable for the post allo transplant setting. We also present the unusual case for successful treatment of PML after allo-HCT via virus specific T-cell therapy.